Gioch - da prekrachish granitsata - Nedeva, Irina; Getov, Andrey (Bulgaria, 2010)
"Stepping across the border" film documents a journey beyond oblivion more than two decades after the forcible name-changing (1984-1985) and the mass deportation (1989) to the Republic of Turkey of thousands of Bulgarian citizens – ethnic turks
Verzio Film Festival Submission
Keywords: Documentary films